2008
DOI: 10.1086/528732
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Enols Are Formed in Plasma Discharges of Alcohols

Abstract: Laboratory low-pressure cold plasma discharges, which are used to simulate some hot core environments in the star-forming region, have been investigated by employing single-photon vacuum ultraviolet ( VUV) photoionization mass spectrometry. Enols with two to four carbon atoms were detected in plasma discharges of alcohols, indicating that enols can result from alcohol destruction induced by ultraviolet and cosmic radiation and accelerated electrons that are abundant in the interstellar medium. This observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
31
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(34 citation statements)
references
References 22 publications
1
31
0
2
Order By: Relevance
“…We previously used this approach to study 90 product chemistry following corona discharges on alkylbenzenes[31;32]. A synchrotron based 91 group also has reported similar electrical dischargeproduct chemistry studies [33][34][35][36]. 92…”
Section: Introduction 55mentioning
confidence: 99%
“…We previously used this approach to study 90 product chemistry following corona discharges on alkylbenzenes[31;32]. A synchrotron based 91 group also has reported similar electrical dischargeproduct chemistry studies [33][34][35][36]. 92…”
Section: Introduction 55mentioning
confidence: 99%
“…Qi et al [14,15] found that enols with two to four carbon atoms were in propanols and butanols fueled flames. Also, it is very interesting that enols can also be formed from plasma discharges of alcohols [16]. Under normal pressure, He et al [9][10][11][12] observed the formation of the enolic species during the partial oxidation of alcohols on Ag/Al 2 catalyst.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, enols with two to four carbon atoms have been found in propanols and butanols fueled low-pressure flames [14,15]. It is very interesting to note that enols can be formed from low-pressure plasma discharges of alcohols as well [16]. In addition, Ferguson et al [17] reported that elevated pressure could accelerate the oxidation reactions showing that the effect of pressure was important for the investigation of the reaction products.…”
Section: Introductionmentioning
confidence: 99%
“…Molecular beam procedures and detection capabilities that have been already well employed in flame/pyrolysis product analysis [19][20][21][22] can be similarly applied in experiments involving discharges. There is now the beginning of similar applications pertaining to plasma chemistry [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%